Educational Migration to Malaysia of Thai Students from Southern Border Provinces - จันทร์อานุภาพ ศันสนีย์; กล้าณรงค์ นิสากร; พิณสุวรรณ ศุภรัตน์; สาแลบิง มูหาหมัด; คุณพิทักษ์ ชีวนันท์; เอียดคง สมสมัย (Parichart Journal, 2017)
This paper aims to (1) study the factors that affect the migration decision making of Thai students for seeking higher education in Malaysia and (2) study the adaption of Thai students in Malaysia. The research methodology comprises of documentary and field research. Thirty-four Thai students in Malaysia originally from Southern border provinces of Thailand generate the core data for this study. Arguably, this research found that the demand for overseas education has been driven by push-pull-supportive factors. Push factors, such as the traditional Thai values place on the growing prestige of international tertiary study. Pull factors, such as fluency in English language when studying overseas. Supportive factors, such as Malaysia is seen as a developed Islamic neighboring country of Thailand. When experiencing culture shock both academically and personally, the typical way that informants adjust themselves to Malaysian society is to integrate into a network of Thai students in Malaysia which could then be their new comfort zones while studying and living abroad